Upaya Guru PAI dalam Meningkatkan Hasil Belajar Siswa Kelas X SMA Negeri 1 Lubuk Basung - Sari, Siska Sentia; Wiza, Rahmi (Al-DYAS, 2023)
This research is motivated by the low student learning outcomes due to the lack of awareness of students to learn. Therefore, there is a need for teacher efforts to increase students' willingness to learn in order to obtain the expected learning outcomes. This study focused on the efforts of PAI teachers in improving the learning outcomes of class X students at SMA Negeri 1 Lubuk Basung with the aim of this study to see how the efforts of Islamic education teachers improve student learning outcomes and the factors that influence them. This type of research uses qualitative research with descriptive methods. Data collection techniques used in this study were observation, interviews and documentation. The results of this study indicate that: (1) the efforts of PAI teachers to improve student learning outcomes are carried out by making class agreements, providing motivation, increasing concentration, using various methods, using media and conducting evaluations (2) Supporting factors for PAI teachers in improving learning outcomes students are supported by adequate school facilities and facilities as well as the enthusiasm of teachers and students in learning. And the inhibiting factors for PAI teachers in improving student learning outcomes are the misuse of cellphones and students' lack of enthusiasm in learning and the strong influence of the outside environment and family environment.